1987
DOI: 10.2307/1938470
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Predation in Age‐ and Size‐Related Habitat Use by Stream Fishes

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Abstract.I examined the effects of age and body size on intra-and interspecific habitat relationships for 15 species of fishes in a natural second-order warm water stream. Juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
296
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(328 citation statements)
references
References 35 publications
27
296
1
4
Order By: Relevance
“…Pêche Piscic. (2002) 365/366 : 297-324 the highest risk of predation in shallow habitats is for large fish, due to non-gape limited predators (birds and mammals) whereas in deeper habitats it is for small fish from gapelimited, piscivorous fish (POWER, 1987;SCHLOSSER, 1987). Some laboratory and field experimental studies have clearly demonstrated that terrestrial predation risk from wading/diving animals is much higher for water-column species in shallow pools than in deep pools and added cover markedly increases their survival (HARVEY and STEWART, 1991;LONZARICH and QUINN, 1995;REINHARDT and HEALEY, 1997).…”
Section: Predationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pêche Piscic. (2002) 365/366 : 297-324 the highest risk of predation in shallow habitats is for large fish, due to non-gape limited predators (birds and mammals) whereas in deeper habitats it is for small fish from gapelimited, piscivorous fish (POWER, 1987;SCHLOSSER, 1987). Some laboratory and field experimental studies have clearly demonstrated that terrestrial predation risk from wading/diving animals is much higher for water-column species in shallow pools than in deep pools and added cover markedly increases their survival (HARVEY and STEWART, 1991;LONZARICH and QUINN, 1995;REINHARDT and HEALEY, 1997).…”
Section: Predationmentioning
confidence: 99%
“…Species richness increases with watershed size (GUÉGAN et al, 1998) and at the local scale with habitat diversity (GORMAN and KARR, 1978;SCHLOSSER, 1982SCHLOSSER, , 1985SCHLOSSER, , 1987. Numerous studies, mainly dealing with the association of upland stream salmonid assemblages with woody debris, revealed the importance of cover as a key factor governing fish distribution (BOUSSU, 1954;GRANDMOTTET, 1983;ANGERMEIER and KARR, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest richness and density occurred during the summer and fall periods, with a total of 23 species and average unit densities ranging from 4.9 to 218.6 fish per 100 m 2 . Others found the same seasonal patterns of use where feeding, resting, evasion from predation, and spawning were the dominant trait strategies [172,178,179,193,194,197,198,201,203,[214][215][216]. Schwartz and Herricks (2008) [79] found that feeding strategy could be summarized as: insectivores mainly occupying the pool-front unit, omnivores in the scour pool unit, piscivores in the pool-mid unit, and herbivores in the glide and riffle with raceway unit.…”
Section: Submerged Barmentioning
confidence: 96%
“…Within the mesohabitat scale, differential habitat use by fish between pools and riffles has been extensively studied [77,123,175,[193][194][195][196][197][198][199]. It was observed from these studies that pools and riffles locally diversify lotic conditions providing strong abiotic environmental controls on fish distribution and abundance.…”
Section: Applied Ecological Concepts At the Mesohabitat Scalementioning
confidence: 99%
See 1 more Smart Citation